Modeling of active thermography through uncertainty quantifi cation of parameters of the heat transfer equation - Arturo Ortiz Tapia; Rumen Ivanov Tsonchev; Mart´ın A. D´ıaz Viera; Marlen Hern´andez Ortiz (Annals of Mathematics and Physics - Peertechz Publications, 2019)
Active thermography is an experimental technique used to analyze samples of materials or entire structures without destroying them, by means of a heat source, such as a laser beam of a given power. It is posed that such experimental procedure can be modeled mathematically through the complete equation of heat transfer.